Catering solutions : for the culinary student, foodservice operator, and ceterer. - Sanders, Edward E.; Mogumbo, Vajava; Fluge, Nick (Upper Saddle River, N.J. : Prentice Hall, 2000)
This book presents many catering solutions for the culinary student, foodservice operator, and caterer.
Keywords: Caterers; Catering; Caterers and catering - Handbooks, manuals, etc